Engaging future professionals in the promotion of active offer for a culturally and linguistically appropriate system - Bouchard, Pier; Vézina, Sylvain; Cormier, Manon; Laforge, Marie-Josée (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
In this chapter, the authors examine the approach of the Consortium national de formation en santé (CNFS) in the area of the active offer of health care and social services in French, in light of ideas from strategic analysis. We will look at the steps the CNFS has taken with regard to a consortium of Francophone post-secondary institutions offering programs in the area of health and social services, to design and share resources to prepare Francophone professionals to take up the challenge of improving access to French-language services in minority settings. In response to a recommendation made in an evaluation report in 2008, the CNFS has undertaken a process to prepare graduates of its post-secondary programs to become ambassadors who are prepared to improve access to safe, quality services for Francophone communities in minority settings. Readers will learn about an actor-centred strategy enabling professionals to provide active offer of services in French. Readers will also learn about the series of challenges, issues, and ideas for action that occur as resources are developed. Because the process is dynamic we conclude by introducing some of the measures now being developed or implemented. Key Words: language and health, issues and challenges of active offer, quality and safety of care, actor, strategy, commitment, education and training.
Chapter 2

L’engagement des futurs professionnels en faveur de l’offre active et d’un système adapté linguistiquement et culturellement - Bouchard, Pier; Vézina, Sylvain; Cormier, Manon; Laforge, Marie-Josée (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Dans ce chapitre, les auteurs proposent de revisiter, à la lumière des propositions de l’analyse stratégique, la démarche empruntée par le Consortium national de formation en santé (CNFS) en matière d’offre active de services sociaux et de santé en français. Le CNFS étant un consortium d’établissements de formation postsecondaire francophones offrant des programmes dans le domaine de la santé et des services sociaux, il sera question de suivre son parcours vers la conception et la transmission d’outils pour préparer les professionnels francophones à relever les défis relatifs à l’accès aux ser vices en français en contexte minoritaire. Nous y verrons comment, en réponse à une recommandation contenue dans un rapport d’évaluation datant de 2008, le CNFS a entrepris une démarche pour faire en sorte que les diplômés issus des programmes qu’il soutient deviennent des ambassadeurs capables d’intervenir pour un meilleur accès à des services de qualité et sécuritaires à l’intention des communautés francophones en situation minoritaire. Le lecteur y découvrira une stratégie axée sur l’acteur selon laquelle un professionnel sensibilisé et outillé serait en mesure d’influencer le système pour améliorer l'offre active de services en français. Il y fera également le constat d’une série de défis, d’enjeux et de pistes d’action qui se sont profilés tout au long de la démarche. Le processus étant dynamique, nous conclurons en présentant quelques mesures en cours d’élaboration ou d’implantation. Mots-clés : langue et santé, enjeux et défis de l’offre active, qualité et sécurité des soins, acteur, stratégie, engagement et formation.
Chapitre 2

Issues and challenges in providing services in the minority language: The experience of bilingual professionals in the health and social service network - de Moissac, Danielle; Drolet, Marie; Savard, Jacinthe; Savard, Sébastien; Giasson, Florette; Benoît, Josée; Arcand, Isabelle; Lagacé, Josée; Dubouloz, Claire-Jehanne (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter explores the experience of bilingual professionals with the provision of health and social services in the official language of minority communities in Canada. Seventy-two professionals from Manitoba and eastern Ontario describe the main issues associated with language access, and the challenges with which they are faced in their day-to-day responsibilities with the active offer of these services. Professionals reported challenges such as shortage of bilingual professionals and services, and difficulty identifying clients who wish for services in the official language of the minority and finding bilingual professionals, as well as lack of organizational support to actively offer services in the minority language in health facilities. Some suggestions to better support the practice of active offer are provided. Key Words: active offer, health and social services, official language, minority communities, professionals.
Chapter 8

Offering health services in French: Between obstacles and favourable factors in Anglophone hospital settings - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Chapter 7

Offre de services de santé en français : entre obstacles et facteurs favorables en milieu hospitalier anglophone - Forgues, Éric; Bahi, Boniface; Michaud, Jacques (Accessibilité et offre active : santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Notre chapitre vise à mettre en relief les facteurs sociaux et organisationnels qui favorisent l’offre de services de santé en français par des professionnels travaillant dans des établissements de santé majoritairement anglophones. Il présente une perspective sociologique qui invite les intervenants à tenir compte de la complexité de l’environnement socio-organisationnel dans lequel pratiquent les professionnels de la santé. Ainsi, leurs compétences linguistiques ne suffisent pas à assurer pareille offre. L’engagement de la haute direction et de ses gestionnaires, la gestion des services et des ressources humaines, les relations de travail, la disponibilité de la main-d’oeuvre bilingue, le contexte juridique et politique sont, entre autres facteurs, des éléments à considérer afin de comprendre dans tous ses aspects la prestation de services de santé en français. Plus largement, ils renvoient nécessairement aux rapports sociaux qu’entretiennent les anglophones et les francophones. Mots-clés : services de santé, environnement socio-organisationnel, droits linguistiques, professionnels de la santé.
Chapitre 7

Active offer, actors, and the health and social service system: An analytical framework - Vézina, Sylvain; Savard, Sébastien (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
This chapter presents a theoretical framework inspired by strategic analysis, also called the sociology of organizations. By adopting this approach, researchers try to uncover the objectives and strategies used by the actors involved in order to better grasp the dynamics of the system of action, while at the same time taking into consideration the constraints arising from the formal structure. The concepts dealt with include the system of action, power, rules of the game, change, strategy, actor, issue, organization, and environment, all of which take into account the complexity of the challenges surrounding the practice of active offer in health and social services. One of the major contributions of this approach is that it provides an analytical framework making it possible to gain a better comprehension of the relationship between the actor and the system. These two components are essential not only for understanding the subject explored here, but also for identifying the strategies for action used by actors in a given community. Key Words: active offer, social services and health, system of action, power, zone of uncertainty, strategic analysis, sociology of organizations, change, strategy, actor, issue, organization, environment.
Chapter 1

Offre active, acteurs et système de santé et de services sociaux : un cadre d’analyse - Vézina, Sylvain; Savard, Sébastien (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Résumé Ce chapitre présente un cadre théorique inspiré de l’analyse stratégique aussi nommée sociologie des organisations. Par cette approche, le chercheur tente de découvrir les objectifs et stratégies des acteurs en présence pour mieux saisir la dynamique du système d’action tout en prenant en compte les contraintes issues de la structure formelle. On y traite des concepts de système d’action, de pouvoir, de règle du jeu, de changement, de stratégie, d’acteur, d’enjeu, d’organisation et d’environnement, lesquels rendent compte de la complexité des défis entourant la pratique de l’offre active en santé et services sociaux. Une des contributions majeures de cette approche est qu’elle fournit un cadre d’analyse permettant de mieux saisir la relation entre l’acteur et le système, deux composantes essentielles tant à la compréhension de notre objet qu’à l’identification de stratégies d’action par les acteurs du milieu. Mots-clés : offre active, services sociaux et de santé, système d’action, pouvoir, zone d’incertitude, analyse stratégique, sociologie des organisations, changement, stratégie, acteur, enjeu, organisation, environnement.
Chapitre 1